Mendelian randomization analyses suggest a role for cholesterol in the development of endometrial cancer. Issue 2 (7th August 2020) - Kho, Pik‐Fang; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias W.; Black, Amanda; Brinton, Louise; Buchanan, Daniel D.; Chanock, Stephen J.; Chen, Chu; et al.
Abstract: Blood lipids have been associated with the development of a range of cancers, including breast, lung and colorectal cancer. For endometrial cancer, observational studies have reported inconsistent associations between blood lipids and cancer risk. To reduce biases from unmeasured confounding, we performed a bidirectional, two‐sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids (low‐density lipoprotein [LDL] and high‐density lipoprotein [HDL] cholesterol, and triglycerides) and endometrial cancer risk. Genetic variants associated with each of these blood lipid levels ( P < 5 × 10 −8 ) were identified as instrumental variables, and assessed using genome‐wide association study data from the Endometrial Cancer Association Consortium (12 906 cases and 108 979 controls) and the Global Lipids Genetic Consortium (n = 188 578). Mendelian randomization analyses found genetically raised LDL cholesterol levels to be associated with lower risks of endometrial cancer of all histologies combined, and of endometrioid and non‐endometrioid subtypes. Conversely, higher genetically predicted HDL cholesterol levels were associated with increased risk of non‐endometrioid endometrial cancer. After accounting for the potential confounding role of obesity (as measured by genetic variants associated with body mass index), the association between genetically predicted increased LDL cholesterol levels and lower endometrial cancer risk remained significant, especially for non‐endometrioid endometrial cancer. There was no evidence to support a role for triglycerides in endometrial cancer development. Our study supports a role for LDL and HDL cholesterol in the development of non‐endometrioid endometrial cancer. Further studies are required to understand the mechanisms underlying these findings. Abstract : What's new? Some studies have suggested that serum lipids may correlate with endometrial cancer (EC) risk, but results have been inconsistent. In our study, the authors used genetic markers to predict LDL and HDL cholesterol levels and analyze EC risk. They found that when lower LDL or higher HDL levels were predicted, EC risk was increased. These results support a role for LDL and HDL cholesterol in the development of EC, and lipid levels may represent a risk factor for EC. Further studies are required to assess the biological and clinical significance of these associations.